Period-dependent Associations between Hypotension during and for Four Days after Noncardiac Surgery and a Composite of Myocardial Infarction and Death: A Substudy of the POISE-2 Trial. (February 2018) - Sessler, Daniel I.; Meyhoff, Christian S.; Zimmerman, Nicole M.; Mao, Guangmei; Leslie, Kate; Vásquez, Skarlet M.; Balaji, Packianathaswamy; Alvarez-Garcia, Jesús; Cavalcanti, Alexandre B.; Parlow, Joel L.; Rahate, Prashant V.; Seeberger, Manfred D.; et al.
Abstract : Background: The relative contributions of intraoperative and postoperative hypotension to perioperative morbidity remain unclear. We determined the association between hypotension and a composite of 30-day myocardial infarction and death over three periods: (1) intraoperative, (2) remaining day of surgery, and (3) during the initial four postoperative days. Methods: This was a substudy of POISE-2, a 10, 010-patient factorial-randomized trial of aspirin and clonidine for prevention of myocardial infarction. Clinically important hypotension was defined as systolic blood pressure less than 90 mmHg requiring treatment. Minutes of hypotension was the exposure variable intraoperatively and for the remaining day of surgery, whereas hypotension status was treated as binary variable for postoperative days 1 to 4. We estimated the average relative effect of hypotension across components of the composite using a distinct effect generalized estimating model, adjusting for hypotension during earlier periods. Results: Among 9, 765 patients, 42% experienced hypotension, 590 (6.0%) had an infarction, and 116 (1.2%) died within 30 days of surgery. Intraoperatively, the estimated average relative effect across myocardial infarction and mortality was 1.08 (98.3% CI, 1.03, 1.12; P < 0.001) per 10-min increase in hypotension duration. For the remaining day of surgery, the odds ratio was 1.03 (98.3% CI, 1.01, 1.05; P < 0.001) per 10-min increase in hypotension duration. The average relative effect odds ratio was 2.83 (98.3% CI, 1.26, 6.35; P = 0.002) in patients with hypotension during the subsequent four days of hospitalization. Conclusions: Clinically important hypotension—a potentially modifiable exposure—was significantly associated with a composite of myocardial infarction and death during each of three perioperative periods, even after adjustment for previous hypotension. Abstract : This study determined the association between hypotension and a composite of 30-day myocardial infarction and death over three periods: (1) intraoperative, (2) remaining day of surgery, and (3) during the initial four postoperative days. Clinically important hypotension was significantly associated with a composite of myocardial infarction and death during each of three perioperative periods, even after adjustment for previous hypotension.Supplemental Digital Content is available in the text.